IMPLIKASI PERJANJIAN ASEAN-KOREA FREE TRADE AREA (AKFTA) TERHADAP EKSPOR MINYAK DAN GAS BRUNEI DARUSSALAM KE KOREA SELATAN TAHUN 2007 – 2011 - Jihan Ballan; Saimpan Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is an international relations research in economy politic studies which describes about the implications of ASEAN – KOREA FREE TRADE AREA (AKFTA) agreement on exports of oil and gas from Brunei Darussalam to South Korea in 2007 – 2011. The establishment of the ASEAN-Korea Free Trade Area (AKFTA) are to strengthen and develop economies, markets and investments in cooperation between ASEAN and Korean member countries which characterized by gradual liberalization and promote the market of transparent, liberal goods and services and provide facilities for investation.This is qualitative research which used descriptive methods, and collecting datas from some resources like books, journals, official publications and relevant websites. This paper used the neo – liberalism perspective and Free Trade Theory by David Ricardo which known as